RESPON HASIL TANAMAN CABAI RAWIT DI LAHAN GAMBUT DENGAN PERLAKUAN BOKASHI RERUMPUTAN DAN PUPUK NPK 9-20-25 - Faqihudien, Abdul Yusron; Saijo; Arfianto, Fahruddin (Agriculture, 2025)
Chili plants are one of the horticultural plants from the vegetable type that have small fruits with a spicy taste. This study aims to analyze and test the effect of bokashi grass fertilizer and NPK 9-20-25 on peat soil on plant height, stem diameter, fruit weight per plant, number of fruits per plant, fruit weight per grain. The results showed that the treatment of bokashi grass fertilizer and NPK did not affect plant height, stem diameter, number of fruits per plant, fruit weight per plant. Single treatment of bokashi grass fertilizer affected plant height, stem diameter, number of fruits per plant, fruit weight per plant. Efficient treatment to obtain the sweetness level of sorghum stems is the treatment of bokashi grass fertilizer at a dose of 15 tons/ha. The highest results in this study obtained a plant height of 39.01 cm, stem diameter 8.67 cm, fruit weight per plant 32.93 g, number of fruits per plant 23, 24 fruits, fruit weight per grain 1.45 g. For better results, it is recommended to use grass bokashi fertilizer with a dose of 15 t ha-1 and cultivate cayenne pepper plants in seasons that do not have high rainfall.